Da individuação em Simondon ao inventar-se pela educação infantil - Barros, Gustavo de Almeida (2015)
That bibliographic theoretical-characterized survey has been as its beginning the following question: How is an individual constituted? By searching the solution for this question, we have mainly based on the thesis of Gilbert Simondon, a French philosopher, The Individuation under the Light of Notions about Shape and Information (1958), which along with the comprehension about his concepts, sought in natural sciences like inequality, meta stability and transduction. That permitted not only to understand the individual from his individuation process, but also to realize an occurring reality that antecedes it a reality that Simondon himself called pre individual. Moreover, since Simondon show us that the being is never to individuate himself, that pre-individual reality both coexists with the individual and will be his genesis. This point in Simondon s philosophy will make possible for us to answer our own questions. Would the individuation processes not be distinguishing processes, too? In case affirmative, would these singularization processes not be a deindividuation, too? In order to answer our own questions, we have performed, face to Simondon s proposal surveys about the philosophy of difference proposed by the French philosopher Gilles Deleuze and the psychoanalyst Felis Guattari, and by Deleuze s comments about Simondon s philosophy. We have permitted ourselves, therefore, to perform an approach to education, which led us, not only to propose a new manner of understanding education, but also rethinking its practices. For that, we have had to delimitate a theoretical field made up by so many other surveys and texts, which could approximate to what we have performed, that is, which worked out with Simondon, the philosophy of difference and education.